Manifestations of severe portal hypertension: Validation of a non-invasive score in cirrhotic patients - Afonso,Miguel (2012)
BACKGROUND AND AIMS: Current Guidelines recommend that cirrhotic patients should undergo upper gastrointestinal endoscopy for screening of esophageal varices. Several studies evaluated the ability of non-invasive markers to predict the presence of esophageal varices. We aimed to test the validity of platelet count-to-spleen diameter ratio (PC/SD) to predict the presence of esophageal varices as well as endoscopic signs of severe portal hypertension (large varices, red signs on esophageal varices and severe portal hypertensive gastropathy) using the 909 cut-off value. PATIENTS AND METHODS : Retrospective study of 170 cirrhotic patients, who underwent screening for esophageal varices. Liver cirrhosis etiology, laboratory, ultrasonography and endoscopy data were analyzed. STATS: Mann-Whitney test, X2, ROC curves. RESULTS: 170 patients (55 female) were included. One hundred and three (60,6%) had esophageal varices (34,1% large; 11,8% with red signs). Ninety-seven patients (57,1%) had portal hypertensive gastropathy (PHG): with severe PHG in 38 (22,3%). PC/SD <909 was documented in 93 patients. It was significantly associated with the presence of esophageal varices (P<0,001; AUROC= 0,84) and high-risk esophageal varices (large varices or red signs - P<0,001; AUROC= 0,8). The score was also significantly associated with the presence of severe portal hypertensive gastropathy (P<0,001; AUROC= 0,63). CONCLUSIONS: PC/SD is significantly associated with the presence of esophageal varices and portal hypertensive gastropathy. A PC/SD ≥909 is a good predictor of the absence of high-risk varices or severe portal hypertensive gastropathy